Association of serum osteocalcin levels with glucose metabolism in trauma patients. Issue 36 (4th September 2020) - Yang, Yanping; Zhong, Weixi; Huang, Jianyin; Geng, Lei; Feng, Qiming
Abstract : Abstract: Osteocalcin (OC) is an endocrine hormone that regulates glucose metabolism. The aim of this study was to investigate the relationship between serum OC levels and glucose metabolism after trauma. This was a retrospective study of trauma patients admitted to the Department of Emergency Medicine between October 2017 and April 2019. Age, height, weight, injury severity score, and previous medical history were recorded. Serum N-terminal mid-fragment of OC (N-MID OC), hemoglobin Alc (HbA1c), fasting plasma glucose (FPG), fasting insulin (FINS), C-peptide, and other biochemical indicators were measured. Differences between the HbA1c-L (HbA1c <6.5%) and HbA1c-H (HbA1c ≥6.5%) groups were compared. The association of N-MID OC with indicators of glucose metabolism was analyzed. Out of 394 trauma patients, leukocyte and FPG levels in the HbA1c-H group (n = 93) were higher ( P < .05), while N-MID OC levels were lower ( P = .011) than the HbA1c-L group (n = 301). N-MID OC was negatively correlated with HbA1c in the total population ( r = -0.273, P < .001) as well as in the HbA1c-L ( r = -0.289, P < .001) and HbA1c-H ( r = -0.390, P < 0.001) groups, and was positively correlated with C-peptide in the HbA1c-H group ( r = 0.395, P < .001). The different quartiles in the HbA1c-L showed that N-MID OC declined with increasing HbA1c, which was higher than N-MID OC levels in the HbA1c-H group. Multiple linear regression analysis revealed that serum HbA1c was independently associated with serum OC levels after trauma (β=-1.608, P < .001). This study strongly suggests the importance of serum OC on glucose metabolism in trauma patients. HbA1c is independently associated with serum OC levels.